Challenges And Risks In Ghana's Microfinance Sector: Is The Islamic Alternative Any Better? - Mustapha Abdullah Kuyateh (Penerbit Hellow Pustaka, 2023)
Ghana fares well on some indicators of financial inclusion compared to other Sub-Saharan African countries, and is comparable to lower middle-income countries. However, it lacks a clear strategy for financial inclusion and development of microfinance institutions (MFIs) and other methodologies of making financial services more widely available. This paper summarizes the situation and development of microfinance institutions in Ghana, reviews progress and problems in implementing the BoG regulations for MFIs, highlights current risks and challenges, and proposes strategies for mitigating risks. The analysis includes three different levels: BoG and Government of Ghana (GoG); MFIs and their associations; and the public. It is aimed at providing information on the complex issues in the microfinance sector as a basis for dialogue on concrete reforms.